Pediatric Inflammatory Multisystem Syndrome and Rheumatic Diseases During SARS-CoV-2 Pandemic - Schvartz, Adrien; Belot, Alexandre; Kone-Paut, Isabelle (Frontiers in Pediatrics, 2020)
Globally, the coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), appeared to have a milder clinical course in children compared to adults. As severe forms of COVID-19 in adults included an aberrant systemic immune response, children with chronic systemic inflammatory diseases were cautiously followed. No evidence for a specific susceptibility was identified in this paediatric population. European and US Paediatricians started to notice cases of myocarditis, sharing some features with toxic shock syndrome, Kawasaki disease and macrophage activation syndrome in otherwise healthy patients. Multisystem Inflammatory Syndrome in Children (MIS-C) and Pediatric Inflammatory Multisystem Syndrome (PIMS) have designated this new entity in US and Europe, respectively. Spectrum of severity ranged from standard hospitalization to pediatric intensive care unit management. Most patients had clinical history of exposure to COVID-19 patients and/or SARS-COV2 biological diagnosis. Clinical presentations include fever, cardiac involvement, gastro-intestinal symptoms, cutaneous manifestations, haematological features, or other organ dysfunctions. The temporal association between the pandemic peaks and outbreaks of PIMS seems to be in favour of a post-infectious, immune mediated mechanism. Thus, SARS-CoV2 can rarely be associated to severe systemic inflammatory manifestations in previously healthy children in a different manner from adults highlighting the specific need of COVID-19 research in pediatric population.